Committee I: Indications for pulmonary cytology sampling methods. Issue 12 (18th October 2016) - Michael, Claire W.; Hoda, Rana S.; Saqi, Anjali; Kazakov, Jordan; Elsheikh, Tarik; Azar, Nami; Paul Ohori, N.
Abstract : The Papanicolaou Society of Cytopathology has developed a set of guidelines for pulmonary cytology including indications for bronchial brushings, washings and endobronchial ultrasound‐guided fine needle aspiration, technical recommendations for cytologic sampling, recommended terminology and classification scheme, recommendations for ancillary testing and recommendations for postcytologic diagnosis management and follow‐up. All recommendation documents are based on the expertise of the authors, extensive literature review and feedback from presentations at national and international conferences. This document selectively presents the results of these discussions. The present document summarizes the recommendations for clinical and imaging evaluation of pulmonary lesions along with the indications for cytologic studies regarding these abnormalities. Preprocedural requirements regarding brushing, washing and needle aspiration procedures are discussed also. Diagn. Cytopathol. 2016;44:1010–1023. © 2016 Wiley Periodicals, Inc.